New species and records of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Africa and Asia - Nakládal, Oto; Hlaváč, Peter (Zootaxa, 2018)
New species of Clavigeritae, Monodiger ivoricus sp. n. from Ivory Coast and Disarthricerus bruneicus sp. n. from Brunei are described. New records are given for the following species: Zuluclavodes Hlaváč, 2007 new genus for Zambia, Fustigerinus formicarius Bryant, 1943 (new combination), new genus and species for Ivory Coast and Hoplitoxenus joannae Jeannel, 1960, new genus and species for Cameroon. A new locality in South Africa is recorded for Ischyroceros mirus Reichensperger, 1915.